СТРАТЕГІЧНЕ УПРАВЛІННЯ КОНКУРЕНТНИМИ ПЕРЕВАГАМИ АГРАРНИХ ПІДПРИЄМСТВ В УМОВАХ ЦИФРОВІЗАЦІЇ - Kyfyak, Viktoria (Агросвіт, 2023)
У статті визначено, що стратегічною основою управління конкурентними перевагами аграрних підприємств має стати процесна методологія, в основі якої – оптимізація бізнес-процесів. Описано сучасні виклики до стратегії управління конкурентними перевагами аграрних підприємств. Охарактеризовані такі інструменти імплементації цифрових технологій в процес управління конкурентними перевагами як бенчмаркінг, диверсифікація та реінжиніринг. Практичне значення має систематизація ефектів від цифровізації бізнес-процесів аграрного підприємства та основних цифрових розробок їх досягнення. Описано вплив цифровізації на стратегічний розвиток аграрних підприємств та визначено стратегії формування конкурентних переваг шляхом імплементації цифрових інструментів. Обґрунтовано пропозиції щодо використання цифрових технологій у формуванні стратегії управління конкурентними перевагами аграрних підприємств як необхідну умову їх розвитку в умовах динамічного середовища.
STRATEGIC MANAGEMENT OF AGRARIAN ENTERPRISE COMPETITIVE ADVANTAGES IN DIGITALIZATION CONDITIONS
New social challenges, uncertainties, and risks in the development environment of agrarian enterprises, along with the transformation of strategic vectors, have made it urgent to find effective tools for the strategic management of their competitive advantages, while taking into account the trends of digitalization and other global trends in market relations engineering. The purpose of this article is to develop methodological provisions for the formation and implementation of digital tools in the strategic management of the competitive advantages of agricultural enterprises. The article posits that a strategic approach to managing the competitive advantages of agricultural enterprises should be a process methodology based on the optimization of business processes. We argue that the process approach to managing agrarian enterprises should become a strategic concept for forming competitive advantages in the digitalization era. The article discusses modern challenges to managing the competitive advantages of agricultural enterprises and characterizes the tools of implementing digital technologies in the process of managing competitive advantages, such as benchmarking, diversification, and reengineering. Systematization of the effects of digitalization on the business processes of an agricultural enterprise, and the main digital developments for achieving them, are of practical importance. The influence of digitalization on the strategic development of agricultural enterprises is described, and strategies for forming competitive advantages through the implementation of digital tools are defined. The article proposes the use of digital technologies in forming a strategy for managing the competitive advantages of agrarian enterprises as a necessary condition for their development in a dynamic environment. In conclusion, the article argues that the mechanism for implementing the strategy of achieving competitive advantages by agricultural enterprises in the conditions of digitalization is a complex of directions, measures, and tools aimed at achieving a competitive position in the market by introducing advanced technologies into business processes. This allows for achieving a position of leadership in terms of costs, differentiation of products in the market, or the strategy of entering foreign markets.
Keywords: Ключові слова: стратегія управління конкурентними перевагами, конкурентні переваги, аграрні підприємства, бізнес-процес, цифровізація.